Branding Diri Di Era Digital: Pemanfaatan Konten Media Sosial Instagram Mahasiswa Ilmu Komunikasi UIN SU Dalam Menciptakan Identitas Profesional - Yulisda Lubis, Bella; Fazira Lubis, Jasmine; Ns Zalukhu, Ardimas Zain; Rahesya Nasution, Dienaya; Fitri Ritonga, Zulia; Harahap, Nursapia (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2025)
In the digital era that continues to develop, Communication Science students at UIN SU are starting to use social media platforms, especially Instagram to build their professional identity. This research focuses on the strategy of utilizing Instagram social media content by UIN SU Communication Science students. The purpose of this study is to describe how they develop a self-branding strategy through the content they upload. Using a descriptive qualitative approach, this study collected data through in-depth interviews with several respondents and literature studies. The results of the study show that there are strategies, benefits and obstacles experienced by UIN SU Communication Science students. This research is expected to provide insight for other students in utilizing social media as an effective self-branding tool to enter the professional world in the future.